2010
DOI: 10.2139/ssrn.1674903
|View full text |Cite
|
Sign up to set email alerts
|

Commercializing User Innovations by Vertical Diversification: The User-Manufacturer Innovator

Abstract: This paper explores a pathway to commercializing user innovations hitherto not studied, namely, the vertical diversification of a user firm into an upstream industry supplying capital goods, and subsequent coexistence of user and manufacturing units. Such coexistence creates synergies regarding innovation, marketing, and financials. It enables the manufacturing unit to benefit from user innovations in its new product development, while the user unit profits from improved tools. Yet, selling the firm's own user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…On the other hand, another new approach has come the last couple of years to reveal a new approach in the correlation between user-innovators and the manufacturers. This approach, as Block et al (2016) underline, is the approach, which emphasizes in the diversification between user-innovators and manufacturers as a new path way towards the commercialization of users-innovators.…”
Section: Blue Ocean Creation Via Company Transformation and Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, another new approach has come the last couple of years to reveal a new approach in the correlation between user-innovators and the manufacturers. This approach, as Block et al (2016) underline, is the approach, which emphasizes in the diversification between user-innovators and manufacturers as a new path way towards the commercialization of users-innovators.…”
Section: Blue Ocean Creation Via Company Transformation and Innovationmentioning
confidence: 99%
“…As Block et al (2016) state, there are specific synergies between users and manufactures regarding the need knowledge, the solution knowledge, marketing and financials. The benefits for both the two parts, are connected with tight bonds on the way the specific case's conditions are related to innovation, marketing, organization and financials.…”
Section: Blue Ocean Creation Via Company Transformation and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that in engineering-intensive environments, users that are involved should have high professional and technological competencies (Enkel, Perez-Freije, & Gassmann, 2005). There have, however, been reports of companies using so-called embedded users, that is their employees who also use the company's products, to contribute to innovation processes as they are likely to be knowledgeable of both market needs and technological solutions (Block, Henkel, Schweisfurth, & Stiegler, 2016;Roy & Sarkar, 2016). There have, however, been reports of companies using so-called embedded users, that is their employees who also use the company's products, to contribute to innovation processes as they are likely to be knowledgeable of both market needs and technological solutions (Block, Henkel, Schweisfurth, & Stiegler, 2016;Roy & Sarkar, 2016).…”
Section: Users In Cops Innovationmentioning
confidence: 99%
“…Generalizability is a hallmark of this method, as these findings can be tested in other large sample based studies. Block, Henkel, Schweisfurth, and Stiegler (2016) used the "Gioia method" to induce new theory on "user-manufacturer diversification". The authors identified four cases where firms started out as user-innovators and then extended their operations to manufacture and sell the products of their innovative efforts even to competitors.…”
Section: Overview Of Studymentioning
confidence: 99%